Physical layer security in hybrid TPSR two-way half-duplex relaying networks over rayleigh fading channel: non-zero secrecy probability analysis - Phu Tran Tin; Duy Hung Ha; Minh Tran (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, we proposed and investigated the Hybrid TPSR two-way half-duplex (HD) relaying communication networks over rayleigh fading channel in the presence of the eavesdropper (E). The system model consists of two sources A and B communicate with each other with helping of intermediate Relay (R). For the system performance analysis, we analyzed and derived the exact and approximate integral-form of the system Non-zero secrecy probability (NZSP) in the case that the E uses the MRC (maximal ratio combining) technique. In addition, the effect of the main system parameters on the system performance is investigated. Finally, all the research results are convinced by the Monte Carlo Simulation. This paper can provide a novel recommendation for relaying communication network manufacture.